Traumatic tension pneumopericardium and amputation of the left main bronchus - Krawczyk, Lech; Byrczek, Tomasz P.; Łuczyk, Agata; Jagoda, Bogusz D.; Kazanowski, Rafał; Stasiowski, Michał J. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
A 27-year-old woman sustained a blunt chest trauma after a car accident. Computed tomography revealed tension pneumopericardium, bilateral pneumothorax, and a suspected rupture of the left main bronchus. Emergent pericardial needle aspiration was successfully performed. Bronchial amputation was confirmed by bronchofiberoscopy. Despite total detachment of the distal part of the bronchial tree, the ventilation of the left lung was maintained without air leakage by use of pleural drains. Bronchial obturation resulted from the injury, and was effectively treated by bronchoscopic sputum suction at the distal end of the bronchus. Finally, the patient underwent a left thoracotomy with an end-to-end bronchial anastomosis. The patient was discharged home on the 32nd day after the trauma, and no complications were recorded during a 3-month follow-up period.